A New Divergence Free Synthetic Eddy Method for the Reproduction of Inlet Flow Conditions for LES - Poletto, R.; Craft, T.; Revell, A. (Flow, turbulence and combustion, 2013)
This paper describes a recent development of the Synthetic Eddy Method (SEM) proposed by Jarrin et al. (Int J Heat Fluid Flow 30(3):435–442, 2009 ) for generation of synthetic turbulence. The present scheme is designed to produce a divergence-free turbulence field that can reproduce almost all possible states of Reynolds stress anisotropy. This improved representation, when used to provide inlet conditions for an LES, leads to reduced near-inlet pressure fluctuations in the LES and to a reduced development length, both of which lead to lower computer resource requirements. An advantage of this method with respect to forcing approaches (which require an iterative approach) is the suitability for direct usage with embedded LES. Results for a turbulent channel flow are reported here and compared to those from the original SEM, and other direct approaches such as the VORTEX method of Sergent ( 2002 ) and the Synthesized Turbulence approach of Davidson and Billson (Int J Heat Fluid Flow 27(6):1028–1042, 2006 ), showing overall improved performance and a more accurate representation of turbulence structures immediately downstream of the inlet.